Comparative Study of Itopride Hydrochloride in-Vitro Drug Release in Various Brands of Sustained Release Capsules By RP-HPLC - Malik, Anirudha; Raghuvanshi, R.S.; Singh, Gaurav Pratap; Malik, Anirudha; Tonk, Rajiv K. (Journal of Biomedical and Pharmaceutical Research, 2024)
Background: The World Health Organisation has advocated the use of generic medicines to make them accessible and affordable but studies have revealed that marketed products do not produce same therapeutic effects and hence are not interchangeable. Dissolution testing of generic solid dosage forms serves as a valuable tool for acquiring dissolution profiles and for assessing the similarity or dissimilarity between the formulations under examination. Objectives: To evaluate the in-vitro drug release profiles of different generic brands of Itopride Sustained release capsules that are commercially available in Indian market and compare them with the innovator product using model dependant and as well as model independent methods. To determine whether same medicine manufactured by different brands are interchangeable. Materials & Methods: In this study Eight generic brands of Itopride 150mg sustained release capsules available in the Indian market were evaluated using dissolution test with the aim to assess their bioequivalence with the innovator product (Ganaton OD). Dissolution studies were performed using USP type II apparatus at 100 rpm in 900 ml 0.1N HCl while maintaining a temperature of 37±0.5 ºC. The samples were estimated by a validated HPLC method. Dissolution test results were statistically evaluated by employing both model dependant and model independent methods. In model dependant experimental data obtained for each dissolution profile were transformed by applying the equations of different kinetic models and the best-fit model was selected whereas in model independent approach fit factors, dissolution efficiency and mean dissolution times were calculated. Results: The Weibull model best explained the release of drugs from all the brands. Upon statistical evaluation of dissolution test results its was found that while similarity factor f2 was within the limits for all generic brands, difference factor f1 of two brands was out of acceptable range thus questioning their bioequivalency with the innovator product. Also the dissolution efficiency of four out of the brands was out of acceptable limits. Keywords: bioequivalence, difference factor (f1), similarity factor (f2), dissolution profile, comparison and evaluation..